A Peruvian family with a novel PARK2 mutation: Clinical and pathological characteristics. Issue 5 (May 2015) - Cornejo-Olivas, Mario R.; Torres, Luis; Mata, Ignacio F.; Mazzetti, Pilar; Rivas, Diana; Cosentino, Carlos; Inca-Martinez, Miguel; Cuba, Juan M.; Zabetian, Cyrus P.; Leverenz, James B.
Abstract Background Mutations in PARK2 result in autosomal recessive young onset Parkinson's disease (YOPD). Although there have been a number of reports on the clinical characteristics of PARK2-related PD, there is limited information available on the associated neuropathologic changes. Design We describe the clinical and pathological characteristics of a Peruvian family with YOPD. The proband and one unaffected sibling were screened for PARK2 dosage and point mutations. One affected sibling had detailed neuropathologic examination. Setting Instituto Nacional de Ciencias Neurologicas (INCN) in Lima, Peru. Results The proband and two of her four siblings developed YOPD and both parents were unaffected. The clinical course has been characterized by akinetic-rigid parkinsonism predominantly affecting the lower limbs and dyskinesias. Analysis of PARK2 showed that the proband is compound heterozygous for a novel acceptor splice site mutation in intron 5 (IVS5-1G>A) and an exon 7 deletion. Neuropathologic assessment of an affected sibling revealed severe neuronal loss in the substantia nigra (SN) and loss of tyrosine hydroxylase immunopositive fibers in the striatum. No Lewy body pathology was observed using standard histology or immunohistochemistry for α-synuclein. Conclusions Consistent with most neuropathologic reports of patients with PARK2 mutations, we did not observe Lewy body inclusions, despite marked SN degeneration and severe dopaminergic denervation of the striatum. These data describe a novel splice site mutation and further extend the clinicopathological characterization of PARK2-associated PD.